Low Level of Defense Mechanism Portrayed on Joe Goldberg in The First Season of You Series - Devianti, Klarisa; Jumino, Jumino (Sabda: Jurnal Kajian Kebudayaan, 2021)
Joe as the main character is in the spotlight of the You series audience because of his very brutal actions. When the writer viewed it from the perspective of a low-level defense mechanism, this kind of brutality assuredly could have formed. The method used in analyzing this article is library research through primary data, which is by the You series itself, and secondary data from previous research connected with this article. The result of this research is that the influence of Joe's bad past on his family is the origin of the low-level defense mechanism that occurs in Joe causing him to commit physical aggression toward people around Beck by killing them. Hence, it can be concluded that Joe's increased anxiety can make Joe's bad ego affect more and physical aggression occurs.